Siblings in adolescents` sports careers: a systematic mapping review - Rocha, H. P. A. da; Costa, F. R. da; Casas, A. J.; Torregrossa, M. (International Journal of Sport and Exercise Psychology, 2026)
Family is a crucial support system for athletes and several studies focus on parental involvement in athletes` development. However, only a handful explore how sibling relationships affect athletes` sports careers. Thus, through a systematic mapping review, we aimed to explore the role played by siblings in adolescent athletes` sports careers and the effects this role has on the family system. Results showed that the 15 reviewed journal articles were published in English in five countries. Thirteen of them used cross-sectional research designs, while only two journal articles employed a longitudinal design. Research on sibling relationships has shown that they generate both positive and negative feelings, influencing athletes` sports career development in different ways. For instance, increased time spent together through sports participation strengthens emotional bonds, with the older sibling often serving as a source of inspiration for the younger one. Conversely, sibling competition for parental support put more pressure on the athletes and generated negative feelings among them. We discussed how ambiguity in sibling relationships could harm the balance within the family system and lead athletes to withdraw from sports, as their careers require much familial support. In conclusion, families should encourage balanced relationships and less competition among their members to guarantee a healthy environment for the development of athletes, children, and parents. Further studies could explore siblings in athletic careers, considering longitudinal designs and family system approaches.